2023
DOI: 10.1371/journal.pone.0281269
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between psychological flexibility and internet gaming disorder among adolescents: Mediation effects of depression and maladaptive cognitions

Abstract: Psychological flexibility may reduce addictive behaviours by adaptive and flexible emotional and cognitive processes. This study tested a mediation model of internet gaming disorder (IGD) in which psychological flexibility would reduce depression and maladaptive cognitions related to internet gaming and in turn lower the risk of IGD. A cross-sectional study surveyed 2102 secondary 1–4 students from seven schools during March to November 2021 in Hong Kong, China. The results showed that 12.7% and 52.2% of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…It has been reported that patients with IGD exhibit various types of executive dysfunction ( Lee et al, 2020 ). Specifically, recent studies have shown that both individuals with IGD and those at risk of IGD exhibit reduced CF ( Weinstein et al, 2017 ; Yang X. et al, 2023 ). Inflexible cognitive processing may produce maladaptive emotions and cognitive biases that exacerbate IGD-related behaviors ( Zhou et al, 2012 ; Chen L. et al, 2018 ; Tei and Fujino, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that patients with IGD exhibit various types of executive dysfunction ( Lee et al, 2020 ). Specifically, recent studies have shown that both individuals with IGD and those at risk of IGD exhibit reduced CF ( Weinstein et al, 2017 ; Yang X. et al, 2023 ). Inflexible cognitive processing may produce maladaptive emotions and cognitive biases that exacerbate IGD-related behaviors ( Zhou et al, 2012 ; Chen L. et al, 2018 ; Tei and Fujino, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals that are more impulsive spend more time playing video games ( Gentile et al, 2012 ). Regarding CF, recent studies have found an association between reduced CF and the severity of gaming addiction in individuals with internet gaming disorder (IGD) ( Weinstein et al, 2017 ; Yang X. et al, 2023 ). Furthermore, these factors have been reported to play important roles in cue reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological Flexibility (PF) can be described as the ability to either alter one’s behavioral patterns; the ability or willingness to be in contact with our emotions, thoughts, or sensations (private events), both wanted and unwanted ( Kashdan and Rottenberg, 2010 ; Cobos-Sánchez et al, 2020 ; Edwards and Lowe, 2021 ; Rizzo and Schwartz, 2021 ; Fang and Ding, 2022 ; Chong et al, 2023 ; Yang et al, 2023 ). It is defined as the ability to fully contact the present moment as a conscious human being, changing or persisting in one’s behavior while doing so serves valued goals ( Kashdan and Rottenberg, 2010 ; Christodoulou et al, 2023 ).…”
Section: From Flexibility To Mental Flexibility: O...mentioning
confidence: 99%
“…Cognitive and Psychological flexibility have been examined in relation to other processes, e.g., Emotional Intelligence (EI), creativity, and beliefs ( Nijstad et al, 2010 ; Elen et al, 2011 ; Arán Filippetti and Krumm, 2020 ; Cobos-Sánchez et al, 2020 ; Rizzo and Schwartz, 2021 ; Wu et al, 2021 ; Yang et al, 2023 ). Specifically, in these domains, flexibility emerged as the ability to adaptively regulate social relationships (Emotional Intelligence), create new connections between ideas (creativity), and influence beliefs.…”
Section: From Flexibility To Mental Flexibility: O...mentioning
confidence: 99%
“…Neural mechanisms of IGD still remains unclear, and there are a few e cient treatments of IGD. Neurobiological research may provide new ideas for intervention and treatment of adolescent IGD [12] .…”
Section: Introductionmentioning
confidence: 99%